Senam Lansia dan Cek Kesehatan Gratis dalam Mewujudkan Lansia Sehat, Mandiri, dan Produktif di Desa Tambakan, Kecamatan Gandusari, Kabupaten Blitar - Yusvidha Ernata; Shinta Masitho Windriyani; Yuskhil Mushofi; Winarno Winarno; Ahmad Junaidi (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Old age is a stage in the human life cycle where the body undergoes a decline in physiological functions, including a decrease in muscle strength, organ function, balance, and metabolism. To maintain body functions, it is necessary to keep moving, one way is through elderly exercise adjusted to the characteristics of old age, accompanied by regular health check-ups. The lack of knowledge among residents regarding elderly health is the main reason for this activity. Simple health checks include measuring blood pressure, blood glucose, and body weight. A community service program titled "Elderly Exercise and Free Health Check-Up to Achieve Healthy, Independent, and Productive Elderly in Tambakan Village, Gandusari District, Blitar Regency". The purpose of this study is to provide health awareness and encourage exercising, one of which is through exercise, to elderly residents in the surrounding area. The elderly appeared very enthusiastic about this activity; health results show that most are in normal condition. A small portion of the remaining elderly, those considered at risk for high blood pressure and high blood glucose, need to be given guidance on a healthy lifestyle. This activity needs to be held continuously, because the elderly have the right to a decent life with healthcare services and the habit of exercising to maintain a long, happy, and healthy life.